Qoheleth : a commentary - Krüger, Thomas, 1959- (Hermeneia--a critical and historical commentary on the Bible., 2004)
The fact that the book, at least at first glance, reveals no clear organization and no overall progression of ideas may be accepted as a literary peculiarity and perhaps even strike one as interesting. Yet when one finds on various themes many statements that are highly contradictory in both the broad and the narrow context, one begins to ask what could be the point of this book and what is the purpose expressed in it. The present commentary seeks to help answer these questions. - p. 1.